Caravaggio - Spike, John T. 1951- (Abbeville Press, 2001)
Accompanying CD-ROM : "contains a file named CARAVA.pdf, which contains a searchable catalogue of the autograph, atrributed, and lost works of ... Caravaggio, with listings of selected copies, and a comprehensive bibliography and list of exhibitions, in .pdf ...".
CD-ROM-Beil. u.d.T.: Caravaggio: Catalogue of paintings
Keywords: Caravaggio, Michelangelo Merisi da <1573-1610>; Caravaggio, Michelangelo Merisi da -- 1571-1610; Longhi, Roberto -- 1890-1970; Schilderijen; Malerei; Painters -- Italy -- Biography; Bibliografie; Italien; Biografie; Werkverzeichnis